Macrophage Migration Inhibitory Factor Limits Renal Inflammation and Fibrosis by Counteracting Tubular Cell Cycle Arrest - Djudjaj, Sonja; Martin, Ina V.; Buhl, Eva M.; Nothofer, Nina J.; Leng, Lin; Piecychna, Marta; Floege, Jürgen; Bernhagen, Jürgen; Bucala, Richard; Boor, Peter (Journal of the American Society of Nephrology, 2017)
Renal fibrosis is a common underlying process of progressive kidney diseases. We investigated the role of macrophage migration inhibitory factor (MIF), a pleiotropic proinflammatory cytokine, in this process. In mice subjected to unilateral ureteral obstruction, genetic deletion or pharmacologic inhibition of MIF aggravated fibrosis and inflammation, whereas treatment with recombinant MIF was beneficial, even in established fibrosis. In two other models of progressive kidney disease, global Mif deletion or MIF inhibition also worsened fibrosis and inflammation and associated with worse kidney function. Renal MIF expression was reduced in tubular cells in fibrotic compared with healthy murine and human kidneys. Bone marrow chimeras showed that Mif expression in bone marrow-derived cells did not affect fibrosis and inflammation after UUO. However, Mif gene deletion restricted to renal tubular epithelial cells aggravated these effects. In LPS-stimulated tubular cell cultures, Mif deletion led to enhanced G2/M cell-cycle arrest and increased expression of the CDK inhibitor 1B (p27Kip1) and of proinflammatory and profibrotic mediators. Furthermore, MIF inhibition reduced tubular cell proliferation in vitro . In all three in vivo models, global Mif deletion or MIF inhibition caused similar effects and attenuated the expression of cyclin B1 in tubular cells. Mif deletion also resulted in reduced tubular cell apoptosis after UUO. Recombinant MIF exerted opposing effects on tubular cells in vitro and in vivo . Our data identify renal tubular MIF as an endogenous renoprotective factor in progressive kidney diseases, raising the possibility of pharmacologic intervention with MIF pathway agonists, which are in advanced preclinical development.